A corrosion evaluation of mild carbon steel in reclaimed refinery stripped sour water. (15th October 2020) - Bastos, Pedro D.A.; Bastos, Alexandre C.; Ferreira, Mário G.S.; Santos, Maria António; Carvalho, Pedro J.; Crespo, João G.
Abstract: Reclaiming water for cooling systems in oil refineries has been strongly encouraged over the past years for decreasing the large consumption of fresh water, thus contributing to the efficient use of this valuable resource. In a recent study [ Journal of Environmental Management 261 (2020) 110229 ], some of the authors studied the retention of phenols in refinery wastewater through reverse osmosis (RO) and found rejections of up to 98% of phenols and 99% of both chemical oxygen demand (COD) and total organic carbon (TOC). The permeates complied with the quality standards for make-up water in cooling processes. A missing aspect, important for the water to be used in the oil and gas industry, was the level of corrosivity of the new permeates. In this work the corrosion of mild carbon steel in the permeates and in the original cooling tower make-up water was studied by electrochemical techniques. The corrosion rate of steel in the permeates in aerated conditions was lower (between 0.053 ± 0.006 and 0.123 ± 0.011 mm year −1 ) than in the make-up water (0.167 ± 0.030 mm year −1 ), confirming their suitability for replacing make-up water in the cooling towers. The low corrosion of carbon steel was attributed to the low conductivity and absence of oxidizing species in the fluids, compared to fresh water. Highlights: Refinery wastewater is treated by reverse osmosis at the emission source. The reclaimed water meets the standards for makeup water in refinery cooling towers. Corrosion of mild carbon steel is tested in reclaimed and current makeup waters. The corrosion in reclaimed water is lower than in the makeup water.